Host cell-based screening assays for identification of molecules targeting Pseudomonas aeruginosa cyclic di-GMP signaling and biofilm formation - Hu, Ying; Webb, Jeremy Stephen; An, Shi-qi (Frontiers in Microbiology, 2023)
The rapid emergence of bacterial resistance to antibiotics in current use is occurring worldwide and poses a significant threat to global healthcare systems. Recent research to identify new effective anti-bacterial agents has focused on regulatory pathways as targets for interference. Regulatory mechanisms employing intracellular Bis-(3',5') cyclic di-guanylate (c-di-GMP) as a secondary messenger represent a distinct category of subjects. This molecule, c-di-GMP, is present in nearly all bacterial species and plays a pivotal role in governing various biological processes, encompassing antibiotic resistance, biofilm formation, and virulence. Alteration of the cellular concentrations of the nucleotide through modulation of associated signalling pathways has the potential to reduce biofilm formation or increase susceptibility of the biofilm bacteria to antibiotics. Here we have developed a screen for compounds that alter c-di-GMP levels in Pseudomonas aeruginosa in co-culture with bronchial epithelial cells. Through the assay of 200 natural compounds, we were able to identify several substances showing promising effects on P. aeruginosa in a host biofilm infection model. Importantly, we detected compounds that inhibit c-di-GMP levels and showed significant influence on biofilm formation and virulence in P. aeruginosa in vitro and in vivo. Consequently, we offer proof-of-concept information regarding swift and practical drug screening assays, suitable for medium-to high-throughput applications, which target the c-di-GMP signaling pathways in this significant Gram-negative pathogen.